Association of glutathione S-transferase M1 (GSTM1) null genotype polymorphism with the effectiveness of metformin monotherapy in type 2 diabetes mellitus (T2DM) patients - Ni Luh Made Noviana Dewi; Dwi Aris Agung Nugrahaningsih; Dita Maria Virginia (Indonesian Journal of Pharmacology and Therapy, 2026)
Genetic variations may contribute to the development of diabetes and influence individual susceptibility to the disease. One of the relevant genes is glutathione S-transferase M1 (GSTM1). Alterations in the expression of GST enzymes can lead to inefficient detoxification processes. Such genetic variations are believed to contribute to interindividual variability in metformin response, potentially affecting therapeutic outcomes. This study aimed to evaluate the effect of the GSTM1 null genotype on the effectiveness of metformin monotherapy in patients with type 2 diabetes mellitus (T2DM). This was an observational study with a case–control design. The case group consisted of T2DM patients who failed to achieve the target HbA1c level. Detection of the GSTM1 null genotype was performed using polymerase chain reaction (PCR). The association between GSTM1 genotype and the effectiveness of metformin was analyzed using the Chi-square test. Disease risk associated with the genetic polymorphism was assessed by calculating the odds ratio (OR) and 95% confidence interval (CI). There was no significant association between GSTM1 genotype groups and the effectiveness of metformin monotherapy (OR = 0.487; p = 0.318). In conclusion, the GSTM1 null genotype does not significantly influence the therapeutic effectiveness of metformin monotherapy in patients with T2DM.